A trityl condensed ring derivative and electroluminescent device thereof
By using trityl fused ring derivatives as the main luminescent material of OLED devices, the problems of waste of materials and insufficient luminescence efficiency in the prior art are solved, efficient and low-cost OLED devices are achieved, and service life is improved.
Patent Information
- Application Number
- CN202411701450.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-11-26
AI Technical Summary
There is a lot of waste of materials during the preparation process of existing OLED devices, which leads to high production costs and is not conducive to large-scale promotion, and has insufficient luminous efficiency and service life.
Trityl fused ring derivatives are used as the main luminescent material, and by connecting them with fused ring fragments with fluorescent properties, a large-volume rigid structure with a deep HOMO energy level is formed, which improves energy transfer efficiency and avoids exciton annihilation.
It improves the luminous efficiency and service life of OLED devices, achieves low-cost, large-scale production and sustainable production, and the compounds form amorphous film with good stability in the functional layer of the device.
Smart Images

Figure CN119176790B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic luminescent materials and semiconductors, and in particular relates to a trityl condensed ring derivative and an electroluminescent device thereof. Background Art
[0002] Organic light-emitting diode (OLED) technology is an advanced display technology. With its unique self-luminous properties, excellent color performance, wide viewing angle, thin design and flexible display potential, it has been widely used and studied in many fields such as home entertainment, mobile devices, and automotive displays. The development of OLED technology benefits from the cross-integration of multiple disciplines such as materials science, microelectronics engineering, and chemical engineering.
[0003] The typical OLED device structure includes an anode, a hole transport layer (HTL), an emission layer (EML), an electron transport layer (ETL), and a cathode. When a voltage is applied between the anode and the cathode, holes are injected from the anode and then move to the emission layer (EML) through the hole transport layer (HTL); at the same time, electrons are injected from the cathode and move toward the emission layer (EML) through the electron transport layer (ETL). In the emission layer (EML), electrons and holes recombine to form excitons. Excitons transfer energy to the luminescent material, causing the luminescent material to emit light.
[0004] The preparation process of OLED devices is very complicated. In the process of evaporating various functional layer materials, a large amount of material loss will occur, which leads to the waste of raw materials, especially the main luminescent material. Due to its large amount, the loss is more serious. This material waste not only increases the production cost, but also is not conducive to the large-scale promotion of OLED technology. Therefore, it is an urgent problem to explore a main luminescent material from the source that can achieve low cost, large-scale production, sustainable production, and good luminous efficiency. Summary of the invention
[0005] The purpose of the present invention is to overcome the above-mentioned deficiencies of the prior art and provide a trityl fused ring derivative and an electroluminescent device thereof, wherein the trityl fused ring derivative is used as a main luminescent material.
[0006] In order to solve the technical problem, the technical solution of the present invention is: a trityl fused ring derivative, the general structural formula of the trityl fused ring derivative is general formula 1:
[0007] .
[0008] in:
[0009] L 1 is selected from substituted or unsubstituted C6~C30 fused ring aromatic groups; Y 1Selected from substituted or unsubstituted C6~C40 aryl, substituted or unsubstituted C6~C40 heteroaryl;
[0010] The heteroatoms in the heteroaryl group include O, S, N, P, B, and Si, and the heteroaryl group includes benzofuran, benzothiophene, dibenzofuran, dibenzothiophene, benzimidazole, indole, spiro[fluorene-9,9'-oxanthene], spiro[fluorene-9,9'-thioanthene], 8-bromophenanthro[4,5-bcd]furan, and 8-bromophenanthro[4,5-bcd]thiophene.
[0011] Preferably, the L 1 Selected from the structures shown in the following groups:
[0012] , , , , .
[0013] Preferably, the Y 1 Selected from the following groups R 1 -R 10 The structure shown:
[0014] R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , R 8 , R 9 , R 10 .
[0015] Preferably, the trityl fused ring derivative is any one of the following compounds 1 to 188:
[0016] ;
[0017] ;
[0018] ;
[0019] ;
[0020] ;
[0021] ;
[0022] ;
[0023] ;
[0024] ;
[0025] ;
[0026] ;
[0027] ;
[0028] ;
[0029] ;
[0030] ;
[0031] ;
[0032] ;
[0033] ;
[0034] ;
[0035] ;
[0036] ;
[0037] ;
[0038] ;
[0039] ;
[0040] ;
[0041] ;
[0042] ;
[0043] ;
[0044] ;
[0045] ;
[0046] ;
[0047] ;
[0048] ;
[0049] ;
[0050] ;
[0051] ;
[0052] ;
[0053] ;
[0054] ;
[0055] ;
[0056] ;
[0057] ;
[0058] ;
[0059] ;
[0060] ;
[0061] ;
[0062] .
[0063] An electroluminescent device comprises a cathode, an anode and an organic layer located between the cathode and the anode, wherein the organic layer comprises any one or a combination of any two of trityl condensed ring derivatives.
[0064] Preferably, the organic layer includes a hole transport layer, a light-emitting layer and an electron transport layer, and the light-emitting layer includes any one or a combination of any two of Compound 1 to Compound 188.
[0065] Preferably, the light-emitting layer comprises a host light-emitting material and a guest light-emitting material, and the host light-emitting material comprises any one or a combination of any two of trityl fused ring derivatives.
[0066] Preferably, the light-emitting layer comprises a host light-emitting material, a guest light-emitting material and a sensitizer, and the host light-emitting material comprises any one or a combination of any two of trityl fused ring derivatives.
[0067] Preferably, the guest luminescent material is selected from , , One of them, and the mass ratio of the host luminescent material to the guest luminescent material is 97:3~99:1.
[0068] Preferably, the sensitizer is selected from , , One of them, and the mass of the sensitizer accounts for 0.1%~0.5% of the mass of the entire light-emitting layer.
[0069] Compared with the prior art, the advantages of the present invention are:
[0070] (1) The present invention provides a trityl fused ring derivative and an organic electroluminescent device thereof. Since the trityl group itself is a bulky structure, it is connected with a fused ring segment having strong fluorescence properties to form a bulky rigid structure with a deep HOMO energy level, which is conducive to the energy transfer from the host material to the guest material, thereby achieving efficient luminescence of the guest molecule and avoiding the exciton annihilation phenomenon of the guest molecule due to excessive concentration. When the trityl fused ring derivative is used as the host luminescent material in the luminescent layer of an OLED device, the luminescence efficiency and service life of the device can be improved;
[0071] (2) The present invention uses a trityl fused ring main structure as a fixed core, which is a strong fluorescent fragment. When it is adapted with a substituted or unsubstituted C6~C40 aromatic or heteroaromatic group, this adaptation method can finely control the intermolecular stacking of the compound, so that the compound forms an amorphous film with good stability in the device functional layer;
[0072] (3) The synthesis and preparation process of the trityl fused ring derivative of the present invention is simple, the raw materials are readily available, and it is easy to achieve product scale and sustainable production, laying a foundation for the further marketization and commercialization of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0073] Figure 1 , a cross-sectional view of an electroluminescent device of the present invention;
[0074] Figure 2 , the NMR spectrum of compound 35 of the present invention;
[0075] Figure 3 , the NMR spectrum of compound 93 of the present invention;
[0076] Figure 4 , NMR spectrum of compound 160 of the present invention.
[0077] Description of reference numerals:
[0078] 1. Conductive glass, 2. Anode, 3. Hole injection layer, 4. Hole transport layer, 5. Electron blocking layer, 6. Light-emitting layer, 7. Hole blocking layer, 8. Electron transport layer, 9. Electron injection layer, 10. Cathode. DETAILED DESCRIPTION
[0079] The specific implementation mode of the present invention is described below in conjunction with examples. The raw materials and reagents described in the present invention are all commercially available.
[0080] The synthesis process of a trityl fused ring derivative (Compound 1 to Compound 188) of the present invention is described as follows:
[0081] The important intermediate structure involved in the present invention is as follows:
[0082] .
[0083] The synthesis process of some intermediates is as follows:
[0084] Synthesis of intermediate M1:
[0085] .
[0086] Step 1:
[0087] Operation process: triphenylmethane (13.9 g, 0.05 mol), 9-chloroanthracene (21.3 g, 0.1 mol), tributylphosphine (1.0 g, 5 mmol), and THF 150 mL were added into a 250 mL polytetrafluoroethylene-lined autoclave in sequence, sealed, and heated with N 2 The reaction mixture was replaced and pressurized to 0.8 MPa, and heated at 200°C for 6 hours. After the reaction was completed, the mixture was naturally cooled to room temperature, the hydrogen chloride gas was discharged until the pressure gauge returned to zero, the reactor was opened, and the reaction system was transferred to a 1000 mL single-necked flask. The reactor was rinsed with a small amount of THF for multiple times, and the rinse liquid was transferred to the above-mentioned 1000 mL single-necked flask. Most of the THF was concentrated, and EA and water were added for multiple extractions. The organic phases were combined, dried, concentrated, and passed through a silica gel column to obtain 14.6 g of compound M1-1 with a yield of 64.3%, an HPLC content of 99%, and a molecular weight of 455.10 shown by LC-MS.
[0088] Step 2:
[0089] Operation process: Under inert atmosphere, add M1-1 (14.6 g, 0.032 mol), diboric acid pinacol ester (9.8 g, 0.039 mol), potassium acetate (6.3 g, 0.064 mol), 1,4-dioxane 200 mL into a 500 mL three-necked flask, start stirring, heat to 60-65 °C, and then add Pd(dppf)Cl 2 (0.41g, 0.5mmol), and then continue to heat up to reflux reaction for 6~8h until M1-1 reacts completely. The reaction solution is directly filtered, the filtrate is collected, concentrated under reduced pressure, dissolved in 200mL toluene, and then washed with water, the organic phase is dried over anhydrous magnesium sulfate, filtered and concentrated, and after the organic phase passes through the silica gel column, the column liquid is again concentrated under reduced pressure until solids precipitate and then stopped, cooled to 10~15℃, crystallized, filtered, and dried to obtain 16.7g of white solid M1, with a yield of 79.2%, HPLC content of 99%, and LC-MS showing a molecular weight of 547.25.
[0090] Synthesis of intermediate M2:
[0091] .
[0092] Step 1:
[0093] Operation process: Referring to the synthesis process of M1-1, 3-chlorophenanthrene (21.3 g, 0.1 mol) was added to obtain 13.9 g of compound M2-1, with a yield of 61.0%, HPLC content of 99%, and LC-MS showing a molecular weight of 455.13.
[0094] Step 2:
[0095] Operation process: Referring to the synthesis process of M1, M2-1 (13.9 g, 0.031 mol) was added to obtain 15.4 g of compound M2, with a yield of 76.9%, HPLC content of 99%, and LC-MS showing a molecular weight of 547.13.
[0096] Synthesis of intermediate M3:
[0097] .
[0098] Step 1:
[0099] Operation process: referring to the synthesis process of M1-1, 1-bromo-7-acetylnaphthalene (24.9 g, 0.1 mol) was added, the reaction temperature was adjusted to 220 °C for reaction, and other conditions remained unchanged to obtain 14.6 g of compound M3-1, with a yield of 59.3%, HPLC content of 99%, and LC-MS showing a molecular weight of 491.12.
[0100] Step 2:
[0101] Operation process: Referring to the synthesis process of M1, feed M3-1 (14.6 g, 0.030 mol) was added to obtain 15.0 g of compound M3, with a yield of 78.3%, HPLC content of 99%, and LC-MS showing a molecular weight of 539.15.
[0102] Synthesis of intermediate M4:
[0103] .
[0104] Step 1:
[0105] Operation process: referring to the synthesis process of M1-1, add M7-1 (38 g, 0.1 mol) and M2-1 (29 g, 0.1 mol) to obtain 45 g of off-white solid M8, with a yield of 59%, HPLC content of 99%, and LC-MS showing a molecular weight of 405.13.
[0106] Step 2:
[0107] Operation process: Referring to the synthesis process of M1, M4-1 (12.5 g, 0.031 mol) was added to obtain 14.7 g of compound M4, with a yield of 80.5%, HPLC content of 99%, and LC-MS showing a molecular weight of 497.20.
[0108] Synthesis of intermediate M5:
[0109] .
[0110] Step 1:
[0111] Operation process: Referring to the synthesis process of M1-1, 1-chloropyrene (23.9 g, 0.1 mol) was added to obtain 14.3 g of compound M5-1, with a yield of 59.3%, HPLC content of 99%, and LC-MS showing a molecular weight of 479.12.
[0112] Step 2:
[0113] Operation process: Referring to the synthesis process of M1, feed M5-1 (14.3 g, 0.030 mol) was added to obtain 16.1 g of compound M5, with a yield of 79.2%, HPLC content of 99%, and LC-MS showing a molecular weight of 571.20.
[0114] The synthesis implementation process of the preferred compounds 2, 35, 93, 160 and 178 using the above key intermediates is exemplified as follows:
[0115] Synthesis of compound 2:
[0116] .
[0117] Operation process: Under inert atmosphere, add M1 (5.5 g, 0.01 mol), 1-chlorodibenzofuran (2.0 g, 0.01 mol), 40 mL of 1,4-dioxane, potassium carbonate (2.8 g, 0.02 mol), 10 mL of deionized water, Pd(PPh 3 ) 4 (0.12 g, 0.1 mmol), the system was heated to reflux reaction for 18 h until the reaction was completed. The reaction solution was washed with water and separated, the organic phase was passed through a diatomaceous earth funnel and the filtrate was collected and concentrated under reduced pressure to obtain a solid crude product, which was passed through a silica gel column to obtain an off-white solid M2 of 4.1 g, with a yield of 69.3%, an HPLC content of 99%, and a molecular weight of 587.16 shown by LC-MS.
[0118] Synthesis of compound 35:
[0119] .
[0120] Operation process: Referring to the synthesis process of compound 2, feed M3 (5.4, 0.01 mol) was added to obtain 4.1 g of compound 35 with a yield of 67.5%, HPLC content of 99%, and LC-MS showing a molecular weight of 603.16.
[0121] Synthesis of compound 93:
[0122] .
[0123] Operation process: Referring to the synthesis process of compound 2, feed M2 (5.5 g, 0.01 mol) was added to obtain 4.1 g of compound 93, with a yield of 70.2%, HPLC content of 99%, and LC-MS showing a molecular weight of 578.20.
[0124] Synthesis of compound 160:
[0125] .
[0126] Operation process: Referring to the synthesis process of compound 2, feed M4 (5.0, 0.01 mol) was added to obtain 3.9 g of compound 160, with a yield of 67.3%, HPLC content of 99%, and LC-MS showing a molecular weight of 687.20.
[0127] Synthesis of compound 178:
[0128] .
[0129] Operation process: Referring to the synthesis process of compound 2, feed M5 (5.7, 0.01 mol) was added to obtain 4.4 g of compound 178, with a yield of 65.9%, HPLC content of 99%, and LC-MS showing a molecular weight of 673.20.
[0130] The synthesis of other compounds all referred to the synthesis process of compound 2.
[0131] The structures of important reactants involved in the present invention are shown in Table 1.
[0132] Table 1 Structures of important reactants involved in the present invention:
[0133]
[0134] like Figures 2~4 Shown are the NMR spectra of compound 35, compound 93, and compound 160.
[0135] Based on the above trityl fused ring derivative compounds 1 to 188, the preferred compounds are used as the main luminescent material in the test device sample. The basic structure and preparation method of the device adopt the device preparation process technology currently recognized by the industry. The device structure diagram is shown in Figure 1 As shown, the preparation process of the device is specifically described as follows: The test device used in the experimental process includes five parts: an anode, a hole transport layer (HTL), a light-emitting layer (EML), an electron transport layer (ETL) and a cathode. Among them, any one or a combination of any two of the above-mentioned preferred trityl fused ring derivatives are used in the EML area to be used as the main light-emitting material for the evaluation experiment. The specific device preparation is briefly described as follows: A substrate can be used under the first electrode or above the second electrode. The substrates are all glass or polymer materials with excellent mechanical strength, thermal stability, waterproofness and transparency. ITO conductive glass is used in this test process. In addition, the substrate used as a display can also have a thin film transistor (TFT) positive column and a specific display image formed by a combination of positive columns.
[0136] Preferably, the organic layer includes a hole transport layer, a light emitting layer and an electron transport layer, wherein the hole transport layer is located between the anode and the light emitting layer, and the electron transport layer is located between the cathode and the light emitting layer. The light emitting layer includes a host light emitting material and a guest light emitting material. The host light emitting material can be any one or a combination of any two of the trityl fused ring derivatives of the present invention, and the guest light emitting material can be a high performance , , The material is one of the following, and the mass ratio of the main luminescent material to the guest luminescent material is 97:3 to 99:1; further, an appropriate amount of sensitizer can be added to the luminescent layer to improve the luminous efficiency, and the sensitizer is selected from , , The mass of the sensitizer accounts for 0.1% to 0.5% of the mass of the entire light-emitting layer.
[0137] Preferably, the anode is usually a material with a large work function in order to smoothly inject holes into the organic layer. The anode materials that can be used in the present invention include indium tin oxide (ITO), indium zinc oxide (IZO), tin dioxide (SnO 2 ), zinc oxide (ZnO), etc.
[0138] Preferably, the cathode is usually a material with a small work function in order to facilitate the injection of electrons into the organic layer. The cathode materials that can be used in the present invention include: magnesium (Mg), silver (Ag), aluminum (Al), aluminum-lithium (Al-Li), calcium (Ca), magnesium-indium (Mg-In), magnesium-silver (Mg-Ag) and other metals or alloys and organic combinations thereof.
[0139] The functional organic layer can be formed on the electrode by vacuum thermal evaporation, spin coating, printing and the like. The compound used as the organic layer can be organic small molecules, organic macromolecules and polymers, and combinations thereof.
[0140] The hole transport layer can be a hole transport layer (HTL) of a single-layer structure, including a single-layer hole transport layer containing only one compound (which acts as both a hole injection and a hole transport effect) and a composite hole transport layer containing multiple compounds. The composite hole transport layer is composed of a variety of organic hole materials, which are mainly arranged in accordance with the industry-general arrangement of a hole injection layer (HIL), a hole transport layer (HTL), and an electron blocking layer (EBL). In the present invention, the hole injection layer is preferably a p-doped hole injection layer, and the p-doped hole injection layer means a hole injection layer doped with a p-dopant. The p-dopant is a material that can impart p-type semiconductor properties. The p-type semiconductor property means the property of injecting holes or transporting holes at the HOMO energy level, that is, the property of a material with high hole conductivity. The light-emitting layer is located between the hole transport layer and the electron transport layer. The main light-emitting material can be any one or any combination of compounds 1 to 188 in the trityl fused ring derivatives of the present invention. The guest light-emitting material can be used in combination with one of the DP-1, DP-2, and DP-3 materials with excellent performance, and the mass ratio of the main light-emitting material to the guest light-emitting material is preferably 98:2; further, an appropriate amount of sensitizer can be added to the light-emitting layer to improve the luminous efficiency. The sensitizer is selected from one of S-7, S-49, and S-50, and the mass of the sensitizer accounts for 0.2% of the mass of the entire light-emitting layer. After the functional layer used to realize organic light emission is prepared, the electron transport material is evaporated on the light-emitting layer. The electron transport material can be realized by one or more combinations of E1, E2, or E3 with excellent industry performance. After the electron transport material is evaporated, the electron injection material is evaporated, followed by sputtering of the metal cathode. Finally, the device is packaged using the industry's common device packaging method. The samples used to test the device are prepared into 30mm×30mm samples, and then the luminescence performance indicators and device efficiency of the above samples are tested. Compared with conventional luminescent materials, the device has better luminescence performance, efficiency and stability.
[0141] Device comparison examples 1~3:
[0142] The organic electroluminescent device was prepared by following the steps below:
[0143] Under high vacuum conditions, on the cleaned conductive glass substrate 1, 25nm thick indium tin oxide (anode 2), 10nm thick HT1 and P1 (used as p-dopant) mixture (the mass ratio of the two is 97:3) as hole injection layer 3, 50nm thick HT-1 as hole transport layer 4, and 10nm thick HT-1 as hole transport layer 5 were successively deposited. EB-1 electron blocking layer 5, after the electron blocking layer is evaporated, a light-emitting layer 6 with a film thickness of 30nm is prepared, and its structure includes one of CDBP or TCTA used in the OLED light-emitting layer as the main light-emitting material, and DP-1, DP-2 or DP-3 as the guest light-emitting material, and the mass ratio of the main light-emitting material to the guest light-emitting material is 98:2 (Comparative Examples 1~2); or one of CDBP or TCTA is used as the main light-emitting material, DP-1, DP-2 or DP-3 is used as the guest light-emitting material, and one of S-7, S-49 or S-50 is used as a sensitizer, and the mass ratio of the three is 98:2:0.2 (Comparative Example 3). On the light-emitting layer, HB-1 with a film thickness of 16nm is evaporated as a hole blocking layer 7. On the hole blocking layer, E1 is evaporated, and the vacuum evaporated film thickness of this material is 25nm, as an electron transport layer 8. On the electron transport layer, a LiF layer with a thickness of 10 nm is formed by a vacuum evaporation device. This layer is the electron injection layer 9. On the electron injection layer, an Al electrode layer with a thickness of 50 nm is formed by a vacuum evaporation device. This layer is the cathode 10. Finally, the test device is packaged after the cover layer material is evaporated, and the test device preparation process is completed. Figure 1 The device shown.
[0144] The detailed preparation scheme is as follows:
[0145] Device Comparative Example 1: Conductive glass / Indium Tin Oxide (25nm) / HT1: P1=97:3(10nm) / HT-1(50nm) / EB-1 (10nm) / CDBP: DP-1=98:2 (30nm) / HB-1(16nm) / E1(25nm) / LiF(10nm) / Al(50nm);
[0146] Device Comparative Example 2: Conductive glass / Indium Tin Oxide (25nm) / HT1: P1=97:3(10nm) / HT-1(50nm) / EB-1 (10nm) / TCTA: DP-1=98:2 (30nm) / HB-1(16nm) / E1(25nm) / LiF(10nm) / Al(50nm);
[0147] Device comparison example 3: conductive glass / indium tin oxide (25nm) / HT1: P1=97:3(10nm) / HT-1(50nm) / EB-1 (10nm) / CDBP: DP-1: S-7=98:2:0.2(30nm) / HB-1(16nm) / E1(25nm) / LiF(10nm) / Al(50nm).
[0148] Device Example 1~Example 11:
[0149] The preparation method of device comparison example 1 is followed, except that the main light-emitting material CDBP is replaced with the trityl fused ring derivatives described in the present invention in sequence: compound 9, compound 12, compound 21, compound 33, compound 47, compound 65, compound 81, compound 93, compound 121, compound 149, and compound 177.
[0150] Device Examples 12 to 17:
[0151] The preparation method of device comparison example 3 was followed, except that 0.2% of a sensitizer was added to the light-emitting layer, and the main light-emitting material CDBP was replaced with compound 65, compound 81, compound 93, compound 121, compound 149, and compound 177 in sequence.
[0152] The conventional materials used in the above device preparation process involve the following functional layer material structure:
[0153] , , , , , , , , , , .
[0154] The performance test data of the multilayer composite structure test device and the control device prepared by using the compound of the present invention are summarized in the following test device result summary table 2 (Note: SM is the abbreviation of "compound"):
[0155] Table 2
[0156]
[0157] As shown in Table 2, from the device test data, the test device prepared using the preferred compound of the present invention as the main luminescent material has a significantly lower driving voltage, significantly improved thermal stability, and longer service life compared with the traditional luminescent material. It can be seen that the device prepared by using the preferred compound of the present invention as the main luminescent material and adding 0.2% of the sensitizer in the luminescent layer: the current efficiency is increased by more than 50%, the maximum power efficiency is increased by more than 25%, the service life is increased by more than 40%, and the overall device efficiency is significantly improved, which has potential value for its promotion and application.
[0158] Compared with Examples 1 to 5 of the present invention and Examples 6 to 11, the device test data of Examples 1 to 5 are slightly inferior, which may be because the corresponding compounds 65, 81, 93, 121, 149, and 177 in Examples 6 to 11 contain fully deuterated phenyl groups. After the "D" atom is introduced into the compound molecule, the spin-orbit coupling effect of the compound molecule will be enhanced, which will increase the intersystem crossing (ISC) ability of the electrons in the molecule, increase the radiative transition rate of the molecule, and reduce the non-radiative transition rate, thereby facilitating the improvement of the quantum efficiency of the guest phosphorescent material.
[0159] The invention discloses a trityl fused ring derivative and an organic electroluminescent device thereof. When the trityl fused ring derivative is used as a main luminescent material in a luminescent layer of an OLED device, the luminescent efficiency and service life of the device can be effectively improved. The invention uses a trityl fused ring main structure as a skeleton, and the structure belongs to a strong fluorescent fragment. When the trityl fused ring main structure is adapted to an aromatic hydrocarbon or heteroaryl group of C6 to C40, the adaptation method can effectively finely regulate the intermolecular stacking of the compound, so that the compound forms an amorphous film with good stability in a functional layer of the device. The trityl fused ring derivative disclosed by the invention has a simple synthesis and preparation process, and the raw materials are easily available, so that the product scale and sustainable production can be easily realized.
[0160] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the field without departing from the purpose of the present invention. Many other changes and modifications can be made without departing from the concept and scope of the present invention. It should be understood that the present invention is not limited to specific embodiments, and the scope of the present invention is defined by the appended claims.
Claims
1. A trityl fused ring derivative, characterized in that: The general structural formula of the trityl fused ring derivative is General Formula 1: ; Wherein: L1 is selected from the structure shown in the following groups: ; Y1 is selected from the following groups R7-R 10 The structure shown: 。 2. A trityl fused ring derivative, characterized in that: The trityl fused ring derivative is any one of the following compounds: ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; 。 3. An electroluminescent device comprising a cathode, an anode and an organic layer located between the cathode and the anode, characterized in that: The organic layer comprises any one or a combination of any two of the trityl fused ring derivatives as described in any one of claims 1 or 2.
4. The electroluminescent device according to claim 3, wherein the organic layer comprises a hole transport layer, a light emitting layer and an electron transport layer, wherein: The light-emitting layer comprises any one or a combination of any two of the trityl fused ring derivatives as described in any one of claims 1 or 2.
5. The electroluminescent device according to claim 4, wherein the light-emitting layer comprises a host light-emitting material and a guest light-emitting material, wherein: The host luminescent material includes any one or a combination of any two of the trityl fused ring derivatives as described in any one of claims 1 or 2.
6. The electroluminescent device according to claim 4, wherein the light-emitting layer comprises a host light-emitting material, a guest light-emitting material and a sensitizer, wherein: The host luminescent material includes any one or a combination of any two of the trityl fused ring derivatives as described in any one of claims 1 or 2.
7. An electroluminescent device according to claim 5, characterized in that: The guest luminescent material is selected from One of them, and the mass ratio of the host luminescent material to the guest luminescent material is 97:3~99:
1.
8. An electroluminescent device according to claim 6, characterized in that: The guest luminescent material is selected from One of them, and the mass ratio of the host luminescent material to the guest luminescent material is 97:3~99:
1.
9. An electroluminescent device according to claim 6, characterized in that: The sensitizer is selected from One of them, and the mass of the sensitizer accounts for 0.1%~0.5% of the mass of the entire light-emitting layer.
Citation Information
Patent Citations
Indenofluorene derivative and electroluminescent device thereof
CN118724670A
Fused cyclic compound, and preparation method and use thereof
US20200006669A1